HYBRID MARKETING STRATEGIES IN SMEs: A PRISMA BASED SYSTEMATIC REVIEW ON MARKET AND ENTREPRENEURIAL ORIENTATION ON SUSTAINABLE COMPETITIVE ADVANTAGE - Natalia Magdalena R Mamulak; Adri Gabriel Sooai; Agustinus Haryanto Pattiraja (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
Small and Medium Enterprises (SMEs) are vital to global economic growth, particularly in Southeast Asia, and significantly contribute to GDP and employment creation. However, financial, human, and technological constraints often hinder their marketing capabilities. The accelerating pace of globalization, rapid digitalization, and post-COVID-19 market volatility demand adaptive and innovative marketing strategies. This study conducts a comprehensive synthesis of SME marketing strategies through a Systematic Literature Review (SLR) following the PRISMA 2020 protocol, drawing from Scopus, Web of Science, and Emerald Insight between 2020 and 2025. Keywords include market orientation, entrepreneurial marketing, branding, digital marketing, pricing, promotion, and distribution. From an initial 5,739 publications, 23 studies met the inclusion criteria and were thematically analyzed based on three research questions: conceptualization and implementation of market orientation, prevalent strategic marketing practices, and management of branding, pricing, communication, and distribution. Findings reveal SMEs increasingly adopt hybrid approaches that combine traditional methods with digital innovations such as social media, e-commerce, analytics, and customer relationship management (CRM). Integrating market orientation (MO) and entrepreneurial orientation (EO) enhances resilience and competitive advantage, while digital readiness and platform dependency persist. This review provides valuable insights for policymakers, academics, and SME practitioners to improve marketing practices and drive sustainable growth in a rapidly changing business environment. Future research should focus on expanding geographic diversity and exploring the long-term impact of digital tools and hybrid marketing strategies.